CONFLICTOGENETY LEVEL OF THE CONCEPTUAL FIELD “WEALTH / POVERTY” IN THE LINGUISTIC CONCIOUSNESS OF RUSSIANS AND THE CHINESE - Chulkina, N.L.; Koltsova, N.V. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The article is devoted to the comparative analysis of the perception of poverty and wealth in Chinese and Russian world view and indification of the conflictogenity level of the units included in the “wealth/poverty” conceptual field. The topicality of the research is reasonable for necessity to study the above said concepts as the basic cultural values that determine relationships between people in society and the fields of concern. The topic is especially actual due to deepening relationships between Russia and China and economic, political and social changes that took place in the countries during the last decades. The target of the research is to reveal conflictogenity level of the the units included in the “wealth/poverty” conceptual field, which is represented in language consciousness of Russians and Chinese and directed at production of optimal strategy and tactics of successful intercultural communication. The basic research methods are cognitive ones (method of measuring the semantic similarity of language units; cognitive interpretation of the study results) and psycholinguistic. To collect data about the conceptual field in language consciousness of Chinese the association experiment was conducted. To research Russian language con-sciousness we used data of association dictionaries.